ANALISIS DAMPAK TEKNOLOGI INFORMASI DALAM PROSES BELAJAR MENGAJAR DI SMA NEGERI 1 SELESAI - Anisa; Hamida Darma; Seget Tritoyoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the impact of information technology use on the teaching and learning process at SMA Negeri 1, which will be completed in the 2024/2025 academic year. Information technology has become a crucial part of education, particularly in supporting a more interactive and efficient learning process. The research method used was a qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that the use of technology such as computers, projectors, the internet, and digital learning platforms (such as Google Classroom and WhatsApp Groups) has a positive impact on increasing student learning motivation, ease of access to materials, and effective communication between teachers and students. However, several obstacles also exist, including limited technological facilities in students' homes, a lack of digital skills among some teachers, and student dependence on technology, which can disrupt learning focus. This study recommends regular training for teachers in the use of learning technology and the provision of digital learning support facilities that are evenly distributed to all students.